2013
DOI: 10.1158/1078-0432.ccr-12-2726
|View full text |Cite
|
Sign up to set email alerts
|

Plasma MicroRNAs as Novel Biomarkers for Endometriosis and Endometriosis-Associated Ovarian Cancer

Abstract: Purpose Endometriosis, a largely benign, chronic inflammatory disease, is an independent risk factor for endometrioid and clear cell epithelial ovarian tumors. We aimed to identify plasma miRNAs that can be used to differentiate endometriosis and ovarian cancer patients from healthy individuals. Experimental design We conducted a two-stage exploratory study to investigate the utility of plasma miRNA profiling to differentiate between endometriosis, endometriosis-associated ovarian cancer (EAOC) and healthy i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(134 citation statements)
references
References 48 publications
4
127
0
3
Order By: Relevance
“…Given the diverse roles that miRNAs play in cellular functions it is not surprising that they play key regulatory roles in the pathogenesisis of EM. Numerous miRNAs are mis-expressed in EM cells and abnormal profiles of miRNAs are reported [Suryawanshi et al 2013]. Some of these miRNA are definitely over-or under-expressed in EM tissues.…”
Section: Epigenetic Regulation Of Emmentioning
confidence: 99%
“…Given the diverse roles that miRNAs play in cellular functions it is not surprising that they play key regulatory roles in the pathogenesisis of EM. Numerous miRNAs are mis-expressed in EM cells and abnormal profiles of miRNAs are reported [Suryawanshi et al 2013]. Some of these miRNA are definitely over-or under-expressed in EM tissues.…”
Section: Epigenetic Regulation Of Emmentioning
confidence: 99%
“…These microRNAs were subsequently further evaluated in a larger cohort. The results showed that plasma microRNA expressing patterns might serve as specific and reliable diagnostic biomarkers (Suryawanshi et al, 2013) resulting in some authors suggesting than microRNA studies will lead to changes in current treatment of both endometriosis and ovarian cancer (Neto et al, 2014).…”
Section: Micrornamentioning
confidence: 99%
“…31,32 The criteria for biomarker selection were 1) dose dependent increase or decrease following PbS-MPA treatment at 5 µg/mL and 50 µg/mL, 2) a change in expression of at least more than threefold following treatment with 50 µg/mL PbS-MPA QDs (in comparison with the untreated control sample), and 3) a statistically significant change in expression level in comparison with that of control sample (P,0.05). Five miRNAs, hsa-miR-525-5p, hsa-miR-527, hsa-miR-532-3p, hsa-miR-548e, and hsa-miR-199a-5p, met the criteria and were proposed as exosomal biomarkers of exposure of HEK293 cells to PbS-MPA.…”
Section: Mirna Expression In Exosomesmentioning
confidence: 99%